Florida 4-H Food Challenge: Event Hosting Guide - Geralyn Sachs (EDIS)
This guide will assist county Extension agents who conduct a Florida 4-H Food Challenge event. It contains contest guidelines, contests responsibilities, sample schedule, orientation talking points, registration template, score tally sheet, Judging questions, contest resources, scoresheets, and worksheets.